(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To reflect on specific recommendations for the prevention of pressure injuries in patients affected by the new coronavirus (COVID-19) in intensive care. Method: theoretical reflection study based on the concept of pressure injury defined by the National Pressure Injury Advisory Panel. Results: the contents were categorized into three thematic axes: specific risk factors for the development of pressure injuries for patients with COVID-19; international recommendations on pressure injuries in patients with COVID-19 and challenges for implementing recommendations for preventing pressure injuries in the face of the COVID-19 pandemic in the Brazilian scenario. Conclusion: to promote the prevention of pressure injuries in intensive care patients with COVID-19 it is essential that health professionals are able to implement advanced interventions, in order to mitigate the intrinsic and extrinsic risks specific to that patient. However, it is essential to recognize potentially preventable lesions, differentiating them from possible inevitable ones, as well as making a differential diagnosis of lesions resulting from the pathogenesis of the virus itself.